PENERAPAN APLIKASI SISBRO BERBASIS WEB DALAM MANENINGKATKAN MANAJEMEN PELANGGAN DI PT.DEACOM TEKNOLOGI: Bisnis Digital - Gunawan, Gunawan; Rahmat Razak, Muhammad Rais; Sofyan, Wahyudi (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
The development of technology has had a significant impact on human life, one of which is the internet, which allows everything to be done more efficiently. PT. Deacom Teknologi has become one of the telecommunications service companies in Sidenreng Rappang Regency. Managing customer data and payments has become a major challenge for PT. Deacom Teknologi as the company grows and the number of customers increases. The manual processes in this context cause various problems such as data errors and delays in payment tracking. To improve efficiency, this research aims to investigate the implementation of the web-based Sisbro application as a solution to facilitate customer data management and enhance payment process efficiency. This research adopts a qualitative analysis approach, emphasizing an in-depth description of the phenomenon under study. The implementation of the web-based Sisbro application at PT. Deacom Teknologi has had a significantly positive impact on improving customer management and the efficiency of the payment process.